THE ROLE OF TEACHER TO ADDRESS ISSUES OF DISRUPTIVE BEHAVIOUR OF STUDENT LEARNERS IN MATHEMATICS CLASSROOMS: A STUDY IN THE SRI LANKAN CONTEXT - Abeygunawardena, K A Vidyanjalie; Vithanapathirana, M V (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Learner’s classroom behaviour has become a global concern due to the intense impacts on academic performance. However, the decline in positive behaviour of learners in the Mathematics classroom impacts the Mathematics instruction in the inclusive classroom. Therefore, this study attempts to identify the role of Mathematics teacher to overcome the negative behaviour manifest by the learners during Mathematics instruction. Data for the mixed research design has collected from 25 Mathematics teachers and 330 learners from randomly selected two schools. The structured questionnaire was given for Mathematics teachers mainly to determine the awareness and applicability of different teaching methods and student behaviour during Mathematics instruction. Subsequently, learners were given a structured questionnaire to overview the perspectives of Mathematics instruction towards their learning styles. Sequentially, 24 classrooms were observed to identify the learner behaviour during mathematics instruction and how it impacts on the existent teaching-learning environment in the inclusive classroom based on the comprehensive checklist developed. Later, semi-structured interviews with teachers were conducted mainly to explore the perceived differences in their Mathematics instructions and written responses to the teacher questionnaire. Focus group discussions with learners were carried out concurrently to investigate the causes of the manifested behaviour during classroom observation. Data were analysed using descriptive analysis and thematic analysis. According to the perspectives of Mathematics teachers, the disruptive behaviour directs learners to deviate from learning Mathematics which creates distractions in the teaching and learning environment in the inclusive classroom. The learners determined that Mathematics instructions have not catered to all learners in the inclusive classroom. Therefore, the applicability of innovative teaching methods is imperative to motivate the learners for active participation in the teaching-learning process. Hence, the transformation of Mathematics instructions towards the learner styles is essential to attain educational objectives by eliminating the disruptive behaviour of learners in the Mathematics classroom.